Analisis Risiko dan Dampak Bencana: Langkah Strategis Penanggulangan Bencana di Desa Rawaurip, Kecamatan Pangenan, Kabupaten Cirebon - Haerul Jamal (UIN Siber Syekh Nurjati Cirebon, 2023)
Apart from being a buffer for environmental ecosystems, the existence of coastal areas also plays a role as a buffer for the economy of the community and the country. Disturbances in coastal areas due to disasters will affect the life of society and the country. This study describes the risks and impacts of disasters that occurred in Rawaurip Village, Pangenan District, Cirebon Regency, and also looks for alternatives in dealing with these disaster risks. This study uses qualitative methods, interview data collection techniques, observation and documentation, as well as data analysis which is guided by the Guidelines for Rapid Environmental Impact Assessment in Disasters Version 5-2018. The results of the study show that the village of Rawaurip has disaster risks in the form of a climate crisis, tidal floods, and abrasion. The impacts arising from the disaster included a decrease in people's income due to damage to salt farms and milkfish ponds due to tidal flooding and unpredictable weather, as well as loss of land owned by the community from abrasion. The recommendations for disaster management are ecosystem reconstruction, planting mangroves, building waterblockers, building embankments and raising pond bunds, improving the quality of coastal area spatial planning, canalization/making canals for drainage channels, and strengthening the capacity of local communities.